The terror : a novel - Simmons, Dan, 1948- (Back Bay Books, 2018)
Their captain's insane vision of a Northwest Passage has kept the crewmen of HMS Terror trapped in Arctic ice for two years without a thaw. But the real threat to their survival isn't the ever-shifting landscape of white, the provisions that have turned to poison, or the ship slowly buckling in the grip of the frozen ocean. The real threat is whatever is out in the frigid darkness, stalking their ship, snatching and brutally killing their fellow seamen. Captain Crozier, who has taken over the expedition after the death of its original leader, Sir John Franklin, draws equally on his strengths as a mariner and on the mystical beliefs of the Eskimo woman he's rescued as he sets a course on foot out of the Arctic and away from the insatiable beast. But every day the dwindling crew becomes more deranged and mutinous, until even Crozier begins to fear there may be no escape from an ever-more-inconceivable nightmare.